Fostering Students’ Critical Awareness Through Critical Media Literacy (2023)
ABSTRACT : This action-research aimed at fostering student’s critical awareness through Critical Media Literacy (CML) by identifying students’ perceptions about a particular TV series using the Empowerment Spiral (ES). It was conducted in a public school in El Carmen de Viboral, Antioquia with 35 fifth graders. Action strategies included exploration of students’ perceptions and assumptions about a TV series. Data gathering instruments included teacher’s journal, students’ artifacts, and a focus group. Findings referred to four caseparticipants’ improvement on; understanding only the explicit messages through the visual features, the ability of going beyond the visual features of the media text to connect and compare violent issues with their life and becoming critically aware when they started to control their interpretations rather than letting the interpretation control them.